2009
DOI: 10.1007/s11277-009-9671-x
|View full text |Cite
|
Sign up to set email alerts
|

Receiver Design for Uplink Multiuser Code Division Multiple Access Communication System Based on Neural Network

Abstract: In this paper, we consider the receiver design problem for the uplink multiuser code division multiple access (CDMA) communication system based on the neural network technique. The uplink multiuser CDMA communication system model is described in the form of space-time domain through antenna array and multipath fading expression. Novel suitable neural network technique is proposed as an effective signal processing method for the receiver of such an uplink multiuser CDMA system. By the appropriate choice of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Zheng et al [89] suggested that non-linearity such as inter-symbol interference and multipath fading in core division multiple access (CDMA) technique can be overcome by using multilayer feed forward neural networks (ML-FFNN). The authors in [89] described that ML-FFNN can efficiently reconstruct the signal removing non-linearity. Similarly, for 4G LTE networks, MIMO-OFDM has been adapted.…”
Section: Role Of Neural Network In Next Generation Networkmentioning
confidence: 99%
“…Zheng et al [89] suggested that non-linearity such as inter-symbol interference and multipath fading in core division multiple access (CDMA) technique can be overcome by using multilayer feed forward neural networks (ML-FFNN). The authors in [89] described that ML-FFNN can efficiently reconstruct the signal removing non-linearity. Similarly, for 4G LTE networks, MIMO-OFDM has been adapted.…”
Section: Role Of Neural Network In Next Generation Networkmentioning
confidence: 99%
“…In the last 2 decades, these researches also picked up the possibility of solving this problem using ANNs. Different architectures of ANNs have been successfully used in DS‐CDMA multiuser detection (MUD) using different training algorithms . All these research activities did not take into consideration the CFAR technique.…”
Section: Related Workmentioning
confidence: 99%
“…Different architectures of ANNs have been successfully used in DS-CDMA multiuser detection (MUD) using different training algorithms. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] All these research activities did not take into consideration the CFAR technique. Note that this technique was considered for the first time in my knowledge by Benkrinah et al 43 but only for nonhomogeneous AWGN channel.…”
Section: Related Workmentioning
confidence: 99%
“…This problem can be resolved by employing highly non-linear classifiers such as artificial neural networks (ANNs) [20]. During the past decade, these ANN models have been extensively utilised as multiuser detectors for code division multiple access system [21][22][23][24][25], but not applied for the SDMA-OFDM system. In this literature, we have tried to explore the possibility of using ANN-based MUD schemes in such systems.…”
Section: Introductionmentioning
confidence: 99%